Phytoplankton dynamics in the Mar Menor, a Mediterranean coastal lagoon strongly impacted by eutrophication. - Ouaissa, Sophia; Gómez-Jakobsen, Francisco; Yebra, Lidia; Ferrera, Isabel; Moreno-Ostos, Enrique; Belando, María Dolores; Ruiz, Juan M.; Mercado, Jesús M. (Elsevier, 2023)
The Mar Menor hypersaline coastal lagoon has suffered serious degradation in the last three decades attributable to nutrient pollution. In 2015, the lagoon experienced an intensive bloom of cyanobacteria that triggered a drastic change of its ecosystem. Our analyses indicate that phytoplankton in 2016–2021 did not present a seasonal variability pattern; the community was mainly dominated by diatoms and punctually reached abundance peaks above 107 cell L- 1 along with chlorophyll a concentrations exceeding 20 μg L- 1. The predominant diatomgenera during these blooms were different as well as the nutrient conditions under which they were produced. These high diatom abundances are unprecedented in the lagoon; in fact, our data indicate that the taxonomic composition, time variation patterns and cell abundance of phytoplankton in 2016–2021 differ notably in comparison to the data published before 2015. Consequently, our results support the finding that the trophic status of the lagoon has changed profoundly.
Keywords: Fitoplancton - Mar Menor (Murcia); Eutroficación; Diatomeas; Dinoflagelados; Criptofíceas; Ecología de lagunas; Eutrophication; Phytoplankton; Cryptophyceae; Diatoms; Dinoflagellates; Mediterranean Sea